«GERMAN-UKRAINIAN DICTIONARY» BY V. KMITSYKEVYCH AND THE UNION IN THE HISTORY OF THE UKRAINIAN LEXICOGRAPHY - Ґрещук, В. В.; Баран, Я. А. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article analyses «German-Ukrainian Dictionary» by V. Kmitsykevych and the Union in the history of the Ukrainian-German lexicography. It justifies the necessity of such a dictionary, supplies brief information on the history of its creation. It highlights the source basis and principles of formation of the dictionary’s register. It analyses the ways of transferring semantics of German lexical units and phrasemes in the Ukrainophonic translated part of the dictionary.